PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP NILAI PERUSAHAAN MANUFAKTUR PESERTA PROPER YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2017 - 2019 - Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The advantage of Green Accounting is that it tries to reduce the negative effects of economic activities and systems on environment. Given the importance of business value and environmental conservation, the assessment of affect the value of the company is very important. This study aims to analyze and examine the factors of green accounting for the value of PROPER Participating manufacturing companies are listed on the Indonesian Stock Exchange. This study uses secondary data obtained from annual reports and sustainability reports of manufacturing companies, PROPER Rating reports and through several related websites and data analysis methods used are multi-linear Regression analysis. Before performing multiple linear regression analysis, classical hypothesistesting is first performed using the program SPSS v.22.